2019
DOI: 10.1111/1744-7917.12709
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression profiles analysis of odorant‐binding proteins in soybean aphid, Aphis glycines (Hemiptera: Aphididae)

Abstract: The soybean aphid, Aphis glycines, is an extreme specialist and an important invasive pest that relies on olfaction for behaviors such as feeding, mating, and foraging. Odorant‐binding proteins (OBPs) play a vital role in olfaction by binding to volatile compounds and by regulating insect sensing of the environment. In this work we used rapid amplification of complementary DNA ends technology to identify and characterize 10 genes encoding A. glycines OBPs (AglyOBPs) belonging to 3 subfamilies, including 4 clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Furthermore, the antennal expression level of OBP7 in the winged aphids at 0 or 2 h (before the peak at 1 day) was the same as that in the wingless aphids during the whole adult stage after 1 day. Thus, once samples at these two time points were selected, it was not surprising that OBP7 expression was not significantly different between winged and wingless aphids, as previously reported in some studies (e.g., Xue et al, 2016;Wang et al, 2019). As after emergence, most OBP genes undergo a process of increased expression and then stabilized, and the time to stabilize was about 1-3 days after emergence (Figure 1).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, the antennal expression level of OBP7 in the winged aphids at 0 or 2 h (before the peak at 1 day) was the same as that in the wingless aphids during the whole adult stage after 1 day. Thus, once samples at these two time points were selected, it was not surprising that OBP7 expression was not significantly different between winged and wingless aphids, as previously reported in some studies (e.g., Xue et al, 2016;Wang et al, 2019). As after emergence, most OBP genes undergo a process of increased expression and then stabilized, and the time to stabilize was about 1-3 days after emergence (Figure 1).…”
Section: Discussionsupporting
confidence: 67%
“…The temporal expression profile of aphids has mainly been compared between the nymph and adult stages (e.g., Xue et al, 2016 ; Wang et al, 2019 ). The expression profiles revealed higher levels of some OBPs in the nymph stage than in adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most important groups of chemo-reception proteins in insects, OBPs have been studied since 1981 (Vogt and Riddiford, 1981). Regarding aphids, OBPs have been widely reported for Acyrthosiphon pisum (Ji et al, 2016) genes encoding complete OBPs with a signal peptide, Zhou et al, 2010), Myzus persicae (Ji et al, 2016), Megoura viciae (Iovinella et al, 2011;Daniele et al, 2018), Sitobion avenae (Kim et al, 2013;Xue et al, 2016), Aphis gossypii (Grabherr et al, 2011;Gu et al, 2013), and Aphis glycines (Grabherr et al, 2011;Wang et al, 2019). Consistent with the simple facultative parasitic lifestyle of aphids, the aphid OBP family has few members, and they are generally more highly conserved than in other insects.…”
Section: Introductionmentioning
confidence: 99%
“…In Batocera horsfieldi Hope, BhorOBP1, BhorOBP2, and BhorOBP3 are expressed in the antennae, but also in the wings, legs, abdomens, maxillary palps, and labial palps (Li et al, 2012). These differences in distribution may be related to their specific features (He et al, 2011;Ma et al, 2016;Wang et al, 2019). Previous studies have shown that OBPs are expressed selectively in different types of sensilla on the antenna, which are considered the minimum functional units for chemoreception.…”
Section: Introductionmentioning
confidence: 99%